Role of Reactive Oxygen Species in Pathogenesis of Radiocontrast-Induced Nephropathy. (29th December 2013) - Pisani, Antonio; Riccio, Eleonora; Andreucci, Michele; Faga, Teresa; Ashour, Michael; Di Nuzzi, Antonella; Mancini, Aldo; Sabbatini, Massimo
Abstract : In vitro and in vivo studies have demonstrated enhanced hypoxia and formation of reactive oxygen species (ROS) in the kidney following the administration of iodinated contrast media, which play a relevant role in the development of contrast media-induced nephropathy. Many studies indeed support this possibility, suggesting a protective effect of ROS scavenging or reduced ROS formation with the administration of N-acetylcysteine and bicarbonate infusion, respectively. Furthermore, most risk factors, predisposing to contrast-induced nephropathy, are prone to enhanced renal parenchymal hypoxia and ROS formation. In this review, the association of renal hypoxia and ROS-mediated injury is outlined. Generated during contrast-induced renal parenchymal hypoxia, ROS may exert direct tubular and vascular endothelial injury and might further intensify renal parenchymal hypoxia by virtue of endothelial dysfunction and dysregulation of tubular transport. Preventive strategies conceivably should include inhibition of ROS generation or ROS scavenging.